Menavigasi Keberlanjutan Hubungan Indonesia-China dalam Sektor Pertambangan dan Energi Pasca Pemilu Tahun 2024 - Mahendra, Yusril Ihza; Setiawati, Siti Muti'ah (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2024)
This research aims to analyze the potential for continuity of Indonesia-China relations in the mining and energy sectors after the 2024 elections. By using the concepts of foreign policy in developing countries and change and continuity, the author argues that the results of the 2024 elections are unlikely to change Indonesia-China relations. Mining and energy cooperation between the two countries has provided great benefits for Indonesia. Currently, China is still Indonesia's largest coal-fired power plant (CFPP) investor, with a total supply of 12,949 MW and 1,800 MW that are still under construction. Furthermore, China's downstream policy has bolstered Indonesia's domestic production capabilities, enabling it to produce semi-finished mineral products like briquettes, coke, semi-coke, upgraded coal, ferronickel, nickel pig iron, and nickel matter at elevated prices. The construction of smelters and large-scale industrial areas has also made Indonesia an important player in the global production chain, controlling 48.48% of the world's total nickel production. We also need to keep in mind that Indonesia is still a developing country, which is undeniably influential in the process of determining foreign policy strategies and goals. As a developing country, economic growth through investment policies will still be the government's main priority. Therefore, the transition of power from President Jokowi to the next government will likely only form a pattern of intensification; that is, it will not change Indonesia-China foreign policy in the mining and energy sectors. This step will be followed by strengthening goals, defining scope, and defining policy strategies to maximize cooperation in an effort to strengthen the position of the two countries in the global mineral and energy supply chain.